2013
DOI: 10.1007/s12565-013-0178-x
|View full text |Cite
|
Sign up to set email alerts
|

A case of retroesophageal right subclavian artery, with special reference to the second intercostal artery, retroesophageal right vertebral artery, and thoracic duct

Abstract: We report a case of retroesophageal right subclavian artery identified in a 59-year-old Japanese female during routine dissection in Nagasaki University School of Medicine. This kind of variation is relatively rare; however, reports of such cases have accumulated. We paid attention to the intersegmental arteries and above all, the second intercostal artery. On the other hand, there have been reports of a retroesophageal right vertebral artery, although such cases are extremely rare.It is considered that both r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…2, 3, 4 mentioned above. The observation in another study also revealed a similar pattern regarding the right vertebral artery arising from the RRSA [23]. Because the number of the bodies analysed is rather small, it is uncertain whether disappearance of the fourth aortic arch, as suggested by the present case, is the dominant form of the RRSA.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…2, 3, 4 mentioned above. The observation in another study also revealed a similar pattern regarding the right vertebral artery arising from the RRSA [23]. Because the number of the bodies analysed is rather small, it is uncertain whether disappearance of the fourth aortic arch, as suggested by the present case, is the dominant form of the RRSA.…”
Section: Discussionsupporting
confidence: 81%
“…Aberrant right subclavian artery (ARSA), also named the arteria lusoria, is an embryologically derived rare variations of aortic arch branching that arises directly from the aortic arch as fourth branch. The reported incidence of ARSA ranges from 0.2% to 1.6% in Japanese [2,9,10,13,14,23,26] and 0.2% to 4.4% of population in other countries [1, 3-5, 7, 11, 12, 15, 19-22, 24, 25, 27, 28]. The retro-oesophageal right subclavian artery (RRSA) is one of the variations of ARSA.…”
Section: Introductionmentioning
confidence: 99%
“…Takemura (1979) 8) , Kitamura (1980) 13) , Emura (1988) 14) , Takemura (1990) 9) , Rahman (1993) 10) , and Kawashima (2001) 15) have reported 1 case of Type 1 respectively. Fujimoto (1963) 3) , Okumura (1974) 12) , and Okamoto (2013) 17) have reported 1 case of Type 2 respectively. Kawai (2011) 16) has reported 2 Type 1 cases, 2 Type 3 cases, and 1 Type 2 case.…”
Section: Thoracic Ductmentioning
confidence: 99%